SAT0523 Efficacy of Local Autologous Platelet Rich Plasma Injection Compared To Local Corticosteroid in Treatment of Plantar Fasciitis; An Ultrasonographic Evaluation. (15th July 2016) - Sherpy, N.A.; Hammad, M.A.H.; Hagrass, E.H.; Samir, H.; Abu Elmaaty, S.; Mortada, M.
Abstract : Background: Plantar fasciitis (PF) is the most common cause of heel pain. Corticosteroid injections are used for cases of PF refractory to conservative treatment. Platelet-rich plasma (PRP) has been gaining popularity as a treatment for PF pain. Objectives: The aim of this study was to compare between local autologous PRP injections and local steroid injections both clinically and sonographically within 3-months regarding its effect on pain, function, thickness, and echogenecity of the plantar fascia and also regarding its safety. Methods: This study was carried out on 50 patients with chronic PF, attending the Rheumatology and Rehabilitation outpatient clinic in Zagazig University Hospitals. Patients were divided into two groups: Steroid group (n=25) and PRP group (n=25). Pre-injection all patients of our study were subjected to full history taking, thorough physical examination, visual analogue scale (VAS: 0–100), Foot Health Status Questionnaire (FHSQ) which included Short Form 36 (SF36), complete blood count (CBC) to exclude anemia and thrombocytopenia, plain x- ray to detect calcaneal spur, and ultrasonography. Patients were reassessed by VAS, FHSQ, and ultrasonography at 1.5 months & 3 months postinjection. The clinical evaluator and sonographer were blinded to the type of injection. Results: We found that at 1.5 months post injection, there was more improvement in the PRP group than the steroid group both clinically and ultrasonographically (p=0.008, p<0.01). Also, although at 3 months no great difference was found between the two groups (p>0.05), PRP patients continued to improve from 1.5 months to 3 months (p=0.000, p<0.01). None of our patients of either groups experienced any complications from injection at the end of the follow-up period. No post-injection foot deformities nor infection were noted (P>0.05). Conclusions: We suggest that the PRP injection is a new, readily available and safe choice of therapy for PF and is not inferior to steroid injection in short term follow up. To our best knowledge this is the first study to compare steroids and PRP by ultrasonography. Disclosure of Interest: None declared